Assessment of Lymph Node Ratio to Replace the pN Categories System of Classification of the TNM System in Esophageal Squamous Cell Carcinoma. Issue 10 (October 2016) - Shao, Yingjie; Geng, Yiting; Gu, Wendong; Ning, Zhonghua; Huang, Jin; Pei, Honglei; Jiang, Jingting
ABSTRACT : Introduction: : The seventh edition of the TNM staging system for esophageal cancer outlined by the American Joint Committee on Cancer (AJCC) defines the N classification on the basis of the number of metastatic lymph nodes. However, this classification is dependent on the actual number of examined lymph nodes. Here in this study, we have focused on revising this N classification system with the metastatic lymph nodes ratio (LNR) and also assessing whether this modification to the current AJCC staging system can better define the prognostic characteristics of esophageal squamous cell carcinoma (ESCC). Methods: : We retrospectively reviewed 916 patients with ESCC who underwent curative resection. Prognostic performance of two staging systems was compared using the Akaike information criterion value and receiver operating characteristics curve. In addition, decision curve analysis evaluated the clinical practical usefulness of the prediction models by quantifying their net benefits. Results: : The univariate and multivariate Cox regression analyses indicated that LNR was an independent risk factor for overall survival. The modified staging system based on LNR had better discriminatory ability, monotonicity, homogeneity, and stratification than the TNM staging system in determining the prognosis of patients with ESCC. However, the decision curves analysis suggested that the modified staging based on LNR has poor clinical practical value over the AJCC TNM staging system. Conclusions: : LNR can supplement the pN categorization system for more effective evaluation of prognosis. But the modified staging system based on LNR has a poor clinical practical value for patients with ESCC compared with the current TNM system and is not superior to AJCC pN staging for ESCC.